Charcot–Leyden crystals and other protein crystals driving type 2 immunity and allergy. (October 2021) - Aegerter, Helena; Smole, Ursula; Heyndrickx, Ines; Verstraete, Kenneth; Savvides, Savvas N; Hammad, Hamida; Lambrecht, Bart N
Abstract : Protein crystals derived from innate immune cells have been synonymous with a Type-2 immune response in both mouse and man for over 150 years. Eosinophilic Galectin-10 (Charcot–Leyden) crystals in humans, and Ym1/Ym2 crystals in mice are frequently found in the context of parasitic infections, but also in diseases such as asthma and chronic rhinosinusitis. Despite their notable presence, these crystals are often overlooked as trivial markers of Type-2 inflammation. Here, we discuss the source, context, and role of protein crystallization. We focus on similarities observed between Galectin-10 and Ym1/2 crystals in driving immune responses; the subsequent benefit to the host during worm infection, and conversely the detrimental exacerbation of inflammation and mucus production during asthma.